REchallenge of NIVOlumab (RENIVO) or Nivolumab-Ipilimumab in Metastatic Renal Cell Carcinoma: An Ambispective Multicenter Study. (18th February 2022) - Vauchier, Charles; Auclin, Edouard; Barthélémy, Philippe; Carril-Ajuria, Lucia; Ryckewaert, Thomas; Borchiellini, Delphine; Castel-Ajgal, Zahra; Bennamoun, Mostefa; Campedel, Luca; Thiery-Vuillemin, Antoine; Coquan, Elodie; Crouzet, Laurence; et al.
Abstract : Introduction . Immune checkpoint inhibitors (ICI) have been approved for front-line therapy in metastatic renal cell carcinoma (mRCC). However, progressive disease often occurs and subsequent therapies are needed. ICI rechallenge may be an option, but there is a lack of data regarding efficacy and prognostic factors. We assessed efficacy of ICI rechallenge and factors associated with better outcomes. Patients and Methods . This ambispective multicenter study included 45 mRCC patients rechallenged with nivolumab ± ipilimumab between 2014 and 2020. Primary endpoint was investigator-assessed best objective response rate (ORR) for ICI rechallenge (ICI-2). Factors associated with ICI-2 progression-free survival (PFS) were evaluated with multivariate Cox models. Results . ORR was 51% ( n = 23) at first ICI therapy (ICI-1) and 16% ( n = 7) for ICI-2. Median PFS was 11.4 months (95% CI, 9.8–23.5) and 3.5 months (95% CI, 2.8–9.7), and median overall survival was not reached (NR) (95% CI, 37.8–NR) and 24 months (95% CI, 9.9–NR) for ICI-1 and ICI-2, respectively. Factors associated with poorer ICI-2 PFS were a high number of metastatic sites, presence of liver metastases, use of an intervening treatment between ICI regimens, Eastern Cooperative Oncology Group performance status ≥2, and poor International Metastatic RCC Database Consortium score at ICI-2 start. Conversely, ICI-1 PFS >6 months was associated with better ICI-2 PFS. In multivariate analysis, there were only statistical trends toward better ICI-2 PFS in patients with ICI-1 PFS >6 months (p = 0.07 ) and toward poorer ICI-2 PFS in patients who received a treatment between ICI regimens (p = 0.07 ). Conclusion . Rechallenge with nivolumab-based ICI has some efficacy in mRCC. We identified various prognostic factors in univariate analysis but only statistical trends in multivariate analysis. Our findings bring new evidence on ICI rechallenge and preliminary but unique data that may help clinicians to select patients who will benefit from this strategy.